The Position Of Muhyi Al Din Darwish On The Grammatical Opinions Of Ibn Khalawayh in I'rab Al-Qur'an Al Karim/ موقف محيي الدين درويشر من آراء ابن خالويه الإعرابية في إعراب القرآن الكريم وبيانه - Marwa Falah Abbas; Wa'd Muhammad Saeed (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study examines Muḥyī al-Dīn Darwīsh’s position toward Ibn Khālawayh’s syntactic views as presented in his work Iʿrāb al-Qurʾān al-Karīm wa Bayānuh, through tracing instances of critical engagement between the two scholars, particularly in syntactic issues where Muḥyī al-Dīn Darwīsh expressed either explicit disagreement or qualified agreement supported by grammatical reasoning. The study is based on the premise that Muḥyī al-Dīn Darwīsh’s stance was not purely negative or dismissive; rather, it was characterized by methodological balance, combining acceptance and rejection according to the strength of the evidence and the soundness of syntactic justification. The study is divided into two sections. The first analyzes the expressions and terminology of rejection employed by Muḥyī al-Dīn Darwīsh in his responses to Ibn Khālawayh, examining their critical connotations and degrees of severity. The second section addresses Muḥyī al-Dīn Darwīsh’s position on Ibn Khālawayh’s syntactic opinions in terms of agreement and disagreement, with particular attention to the grammatical principles upon which his preferences and judgments were based. The study concludes that Muḥyī al-Dīn Darwīsh engaged with Ibn Khālawayh’s views as a critical and investigative grammarian rather than a mere transmitter or imitator. He exercised disciplined scholarly criticism that balanced respect for Ibn Khālawayh’s scientific stature with independent evaluation and preference based on established grammatical rules and Qurʾanic context. This approach reflects a mature critical awareness and a balanced scientific methodology in syntactic analysis.